Stability and Stabilizing of Fractional Complex Lorenz Systems - Rabha W. Ibrahim (Abstract and Applied Analysis)
We study the stability and stabilization of complex fractional Lorenz system. The fractional calculus are taken in sense of the Caputo derivatives. The technique is based on stability theory of fractional-order systems. Numerical solutions are imposed.